Hydrophobic surface functionalization of lignocellulosic jute fabrics by enzymatic grafting of octadecylamine - Dong, Aixue (2015)
Enzymatic grafting of synthetic molecules onto lignins provides a mild and eco-friendly alternative for the functionalization of lignocellulosic materials. In this study, laccase-mediated grafting of octadecylamine (OA) onto lignin-rich jute fabrics was investigated for enhancing the surface hydrophobicity. First, the lignins in jute fabrics were isolated and analyzed in the macromolecular level by MALDI-TOF MS, 1H-NMR, 13C-NMR, and HSQC-NMR. Then, the surface of jute fabrics was characterized by FT-IR, XPS, and SEM. Subsequently, the nitrogen content of jute fabrics was determined by the micro-Kjeldahl method, and the grafting percentage (Gp) and grafting efficiency (GE) of the enzymatic reaction were calculated. Finally, the surface hydrophobicity of the jute fabrics was estimated by contact angle and wetting time measurements. The results indicate that the OA monomers were successfully grafted onto the lignin moieties on the jute fiber surface by laccase with Gp and GE values of 0.712% and 10.571%, respectively. Moreover, the modified jute fabrics via OA-grafting showed an increased wetting time of 18.5 min and a contact angle of 116.72°, indicating that the surface hydrophobicity of the jute fabrics increased after the enzymatic grafting modification with hydrophobic OA molecules.